Differential Effect of Fixed Ratio Magnitude on the Rate of Lever-Pressing and Interinjection Intervals of Cocaine Self-Administration in Rats - Jhanvi N. Desai; Abigail R. Muccilli; Luis E. Tron Esqueda; Jeffrey A. Welge, PhD; Andrew B. Norman, PhD (Elsevier, 2023)
ABSTRACT: Background: Many features of self-administration behavior may be explained by reference to the properties of schedules of reinforcement. Schedules alter the probability of a behavior being reinforced and thereby increase, or decrease, the frequency of the behavior and fixed ratio (FR) magnitude reportedly alters the rate of responding to cocaine. A pharmacokinetic/pharmacodynamic interaction theory states that lever-pressing behavior is induced only when cocaine levels in the body are above the priming/remission threshold and below the satiety threshold-a range termed the compulsion zone. This theory successfully explains cocaine self-administration in rats on a progressive ratio and the FR1 schedule. Objectives: To determine the effects of high FR magnitude on the rate of self-administration of cocaine and the rate of lever-pressing behavior when cocaine levels are within the compulsion zone. Methods: Rats acquired cocaine self-administration on an FR1 schedule and then were switched to sessions that started with FR1 and then FR 5, 10, 20, or 50. An only FR1 session was run each week between FR1/FR50 sessions and then only FR1 sessions were conducted for several weeks. Results: Interinjection intervals at a unit dose of 3 µmol/kg were regular at both FR1 and FR50 but were longer by the time required to complete the 50 presses. When responding by rats was maintained under an FR50 schedule of cocaine presentations, compared to baseline FR1 sessions, dramatic increases in the number of lever-presses were observed after access to cocaine was terminated, a previously unreported finding. However, lever-pressing occurred only when cocaine levels were in the compulsion zone, and this duration was unchanged. The increase in lever-pressing persisted for weeks. Interinjection intervals at FR1 were not altered after exposure to FR50. Conclusions: Although previously considered key to understanding the regulation of cocaine self-administration behavior, FR magnitude simply increased interinjection intervals by the time required to complete 50 lever-presses. The dramatic increase in the rate of lever-pressing was caused by the high FR schedule rather than cocaine. The utility of the schedule-induced increase in the rate of lever-pressing is unclear. The compulsion zone theory provides a rational pharmacological basis for understanding cocaine self-administration behavior.